PEMBINAAN TAMAN PENDIDIKAN AL-QUR’AN (TPA) DI DUSUNSONGBANYU 1, KECAMATAN GIRI SUBO, GUNUNG KIDUL, DAERAH ISTIMEWA YOGYAKARTA - Muntoha Muntoha (Asian Journal of Innovation and Entrepreneurship, 2015)
Taman PendidikanAl-Qur'an (abbreviated as TPA or TPQ) is a body or group ofpeople who organize non-formal type of Islamic religious education which aims to provideinstruction to read the Qur'an at an early age, as well as understand the basics of Islam tokindergarten-aged children, elementary school or madrasah (SD/MI) or even higher.Unfortunately, TPA at Dusun Songbanyu 1, Kecamatan Giri Subo, Gunung Kidul, DaerahIstimewa Yogyakarta that is belonging to the newly established not have a regular scheduleof activitiesand clear. With the usefulness of it, the author also seeks to provide assistancein the form of procurement activities that are routine and consistent. With hope, in thefuture, this activity can be continued independently by Dusun Songbanyu 1.